2009
DOI: 10.1038/sj.bjc.6605320
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trial of short-term neoadjuvant docetaxel and complete androgen blockade in high-risk prostate cancer

Abstract: BACKGROUND: The low probability of curing high-risk prostate cancer (PC) with local therapy suggests the need to study modality of therapeutic approaches. To this end, a prospective phase II trial of neoadjuvant docetaxel (D) and complete androgen blockade (CAB) was carried out in high-risk PC patients. The primary end point was to detect at least 10% of pCRs after chemohormonal treatment. METHODS: Patients with T1c -T2 clinical stage with prostate-specific antigen (PSA) 420 ng ml À1 and/or Gleason score X7 (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 31 publications
5
30
0
4
Order By: Relevance
“…Our data are in concordance with these reports. We observed that the expression of AR and several AR-regulated genes (i.e., ZEB1, IL6, TGFBR3, KLF9) increased in treated tumors, even though serum PSA levels decreased under therapy in most cases, as we previously reported (17). Moreover, high levels of AR correlated with high risk of clinical relapse.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Our data are in concordance with these reports. We observed that the expression of AR and several AR-regulated genes (i.e., ZEB1, IL6, TGFBR3, KLF9) increased in treated tumors, even though serum PSA levels decreased under therapy in most cases, as we previously reported (17). Moreover, high levels of AR correlated with high risk of clinical relapse.…”
Section: Discussionsupporting
confidence: 61%
“…The study included 28 patients with high-risk localized prostate cancer from a previously published, multicenter, phase II trial of neoadjuvant docetaxel plus androgen deprivation followed by radical prostatectomy (17) and 36 control patients with high-risk prostate cancer treated with radical prostatectomy without neoadjuvant treatment. Of the 57 participants in the clinical trial (17), 29 were not included in this study: 23 patients did not consent to participation in the molecular substudy and insufficient material for molecular analysis was available for 6 patients, 3 of whom had a pathologic complete response (pCR) and 3 had microscopic residual tumor (near pCR) in the prostate specimen.…”
Section: Patients and Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the results of studies of taxanes as single agents or in combination with ADT in previously untreated high-risk patients have suggested no enhanced benefit over the use of ADT alone concerning pathologic as well as long-term outcomes, even when the docetaxel was administered every 3 weeks and at doses higher than that in our trial. 2226 Consistently, >75% and approximately 50% of our patients had evidence of respectively residual locally advanced and pelvic LN–metastatic disease after completing treatment, and 9 have died of progressive prostate cancer. Very recent data from a randomized phase III clinical trial (CHAARTED) suggests that, among patients newly diagnosed with metastatic hormone sensitive prostate cancer, those presenting with visceral disease and/or ≥4 bone lesions are the ones that benefit the most from the early use of docetaxel.…”
Section: Discussionsupporting
confidence: 66%
“…This strategy certainly has not been beneficial in breast cancer [39,40], but there is the theoretical potential that exposure to a highly androgen-deficient state, either prior to or simultaneous with chemotherapy, may reduce the efficacy of subsequent taxane-based chemotherapy as taxanes may exert part if not all of their effect [41] by blocking AR nuclear translocation, an effect that may be lost [42] with alternative AR growth pathways activated. To date, this concept has been most closely modelled in the neoadjuvant studies of androgen withdrawal and docetaxel which to date indicate that clinically relevant disease remains despite combination therapies [43,44], and to date, the histological outcomes are no different from neoadjuvant hormonal therapy alone. Nevertheless, this concept will likely require assessment in prospective wellcontrolled studies, although it will be difficult to perceive how such a hypothesis will be practically tested given the suggestion that significant numbers of men will start taking abiraterone prior to chemotherapy in the near future and potential crossover will limit an effect on overall survival.…”
Section: How Long Should Abiraterone Acetate Be Continued After Progrmentioning
confidence: 99%